Clinical and Molecular Analysis in 2 Families With Novel Compound Heterozygous SBP2 (SECISBP2) Mutations - Jiao Fu (2020)
© 2020 Published by Oxford University Press on behalf of the Endocrine Society 2020. Context: Selenocysteine insertion sequence binding protein 2 (SECISBP2, SBP2) is an essential factor for selenoprotein synthesis. Individuals with SBP2 defects have characteristic thyroid function test (TFT) abnormalities resulting from deficiencies in the selenoenzymes deiodinases. Eight families with recessive SBP2 gene mutations have been reported to date. We report 2 families with inherited defect in thyroid hormone metabolism caused by 4 novel compound heterozygous mutations in the SBP2 gene. Case Descriptions: Probands 1 and 2 presented with growth and developmental delay. Both had characteristic TFT with high T4, low T3, high reverse T3, and normal or slightly elevated TSH. The coding region of the SBP2 gene was sequenced and analysis of in vitro translated wild-type and mutant SBP2 proteins was performed. Sequencing of the SBP2 gene identified novel compound heterozygous mutations resulting in mutant SBP2 proteins E679D and R197∗ in proband 1, and K682Tfs∗2 and Q782∗ in proband 2. In vitro translation of the missense E679D demonstrated all four isoforms, whereas R197∗ had only 2 shorter isoforms translated from downstream ATGs, and Q782∗, K682Tfs∗2 expressed isoforms with truncated C-terminus. Reduction in serum glutathione peroxidase enzymatic activity was also demonstrated in both probands. Conclusions: We report 2 additional families with mutations in the SBP2 gene, a rare inherited condition manifesting global selenoprotein deficiencies. Report of additional families with SBP2 deficiency and their evaluation over time is needed to determine the full spectrum of clinical manifestations in SBP2 deficiency and increase our understanding of the role played by SBP2 and selenoproteins in health and disease.